Impact of Transplanting Date and Irrigation Scheduling on Water Balance, Water Productivity and Soil Moisture Movement - Singh, Mahesh Chand; Jain, Anchal Kumar; Jalota, S. K. (Journal of Agricultural Engineering, 2017)
The study investigated the impact of transplanting date and irrigation scheduling on water balance, water productivity, and soil moisture movement in puddled transplanted rice (PTR). Rice transplanted on June 20th (T2) contributed to lesser water losses (ET=75.0 mm and drainage=48.5 mm) than that of June 5th transplanted rice (T1), and significantly saved 164 mm of irrigation water. Treatment T2 resulted in higher irrigation water productivity (WPI=0.19 g.kg-1) and total water productivity (WPI+R=0.08 g.kg-1) than that of treatment T1. In terms of method of irrigation, the irrigation scheduling based on tensiometer (I2-SWS of 16 kPa) contributed to 104.5 mm lesser drainage loss and saved 120 mm irrigation water than that of irrigation scheduling based on intermittent 2-day drainage (I1). Irrigation method I2 contributed to yield higher water productivities (WPI=0.058 g.kg-1 and WPI+R=0.003 g.kg-1) than that of irrigation method I1. The soil moisture movement study was conducted by using hydrus-2D model. The model simulations were compared with the field data. An acceptable agreement between model simulations and field data was achieved.